Serum progesterone concentration on pregnancy test day might predict ongoing pregnancy after controlled ovarian stimulation and fresh embryo transfer - Duport Percier, Marie; Brouillet, Sophie; Mollevi, Caroline; Duraes, Martha; Anahory, Tal; Ranisavljevic, Noemie (Frontiers in Endocrinology, 2023)
Progesterone (P4) is essential for pregnancy. A controlled ovarian stimulation (COS) leads to a iatrogenic luteal defect that indicates a luteal phase support (LPS) at least until pregnancy test day. Some clinicians continue the LPS until week 8 or later, when P4 is mainly secreted by syncytiotrophoblast cells. Measuring serum P4 on pregnancy test day after a fresh embryo transfer could help to identify women who might benefit from prolonged LPS. In women with LPS based on P4 administered by the rectal route, P4 concentration on pregnancy test day was significantly higher in patients with ongoing pregnancy than in patients with abnormal pregnancy. This monocentric retrospective study used data on 99 consecutive cycles of COS, triggered with human chorionic gonadotropin, followed by fresh embryo transfer resulting in a positive pregnancy test (>100 IU/L) (from November 2020 to November 2022). Patients undergoing preimplantation genetic screening or with ectopic pregnancy were excluded. All patients received standard luteal phase support (i.e. micronized vaginal progesterone 600 mg per day for 15 days). The primary endpoint was P4 concentration at day 15 after oocyte retrieval (pregnancy test day) in women with ongoing pregnancy for >12 weeks and in patients with miscarriage before week 12 of pregnancy. The median P4 concentration [range] at pregnancy test day was higher in women with ongoing pregnancy than in women with miscarriage (55.9 ng/mL [11.6; 290.6] versus 18.1 ng/mL [8.3; 140.9], p = 0.002). A P4 concentration ≥16.5 ng/mL at pregnancy test day was associated with higher ongoing pregnancy rate (OR = 12.5, 95% CI 3.61 - 43.33, p <0.001). A P4 concentration ≥16.5 ng/mL at pregnancy test day was significantly associated with higher live birth rate (OR = 11.88, 95% CI 3.30 – 42.71, p <0.001). After COS and fresh embryo transfer, the risk of miscarriage is higher in women who discontinue luteal support after 15 days, as recommended, but with P4 concentration <16.5 ng/mL. The benefit of individualized prolonged luteal phase support should be evaluated.